Design and Testing of E-Commerce Website Shoe Sales with Waterfall Method and User Acceptance Testing (UAT) - Taufik Rahman; Andi Andrean Maulana Putra (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
The development of information technology enables digital transformation in the trading industry, including shoe sales systems. However, many SMEs still face obstacles in the conventional sales process that are less efficient. This study aims to design and test an e-commerce shoe sales website to improve transaction efficiency and user satisfaction. The development method used is Waterfall, which includes needs analysis, design, implementation, testing, and maintenance. Testing was carried out using User Acceptance Testing (UAT) with indicators of ease of use, efficiency, and user satisfaction. The test results showed that the system obtained an average UAT value of 84.3%, indicating strong user satisfaction and effective system performance. With this system, customers can make online orders more easily, while business owners can manage transactions efficiently. This study concludes that the implementation of e-commerce can increase business competitiveness in the digital era. Further research can develop additional features such as integration with digital payment systems and artificial intelligence-based product recommendations to improve user experience.